PEMEKARAN KABUPATEN MUSI RAWAS UTARA DI PROVINSI SUMATERA SELATAN TAHUN 2013-2016 - Rendy Sueztra Canaldhy; Bayu Ady Wijaya; M. Imam Akbar Hairi (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
The Birth of the Act No. 22 of the 1999 on Regional Government and revised by Law Number 32 Year 2004 on Regional Government become a fresh breeze for the region to immediately accelerate of development and prosperity in the region. Musi Rawas Utara (Muratara) be concreate evidence on enactment of Law No. 32/2004. The Problem arise when terms the formation of new autonomous regions must meet three (3) main requirements, namely the Administrative Terms, Conditions Physical and Technical Terms. In this case, some of the terms such as goverment facilities and infrastructure; Sosio-cultural factors; Social adn Politics factor; Defense (Including the boundaries of regions); and security deemed inadequate. Based on the results of research, readiness of the Human Resources to manage their own region are still very limited when viewed from their education levels. Not to mention if you see the political culture society which adopts a parochial and Kaula, provide a loophole for elites and oligarchs be able to infiltrate into the joint life of society and power interfering with the welfare of society. The impact, within a period of three (3) years after the division of the District Muratara designated as disadvantaged areas by the central government.Keywords : Political Autonomy, Musi Rawas Utar.